2006
DOI: 10.1097/01.prs.0000209971.08264.b0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Technique for Wound Closure Using a Barbed Suture

Abstract: The barbed suture represents an innovative option for wound closure. With a cosmesis and safety profile that is similar to that of conventional suture technique, it avoids the drawbacks inherent to suture knots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
139
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 7 publications
4
139
0
4
Order By: Relevance
“…With decreasing reimbursement and rapidly increasing surgical demand, closure time is one target to reduce operative time and cost while increasing operative productivity [1,2,5]. Although knotted interrupted sutures have traditionally been used for TKA capsular closures, they can be time-consuming and may present several potential disadvantages compared with barbed sutures [3]. These include increased focal stitch bulk and stitch abscesses, local tissue ischemia, and increased needle handling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With decreasing reimbursement and rapidly increasing surgical demand, closure time is one target to reduce operative time and cost while increasing operative productivity [1,2,5]. Although knotted interrupted sutures have traditionally been used for TKA capsular closures, they can be time-consuming and may present several potential disadvantages compared with barbed sutures [3]. These include increased focal stitch bulk and stitch abscesses, local tissue ischemia, and increased needle handling.…”
Section: Introductionmentioning
confidence: 99%
“…A running knotless suture technique using barbed suture technology has been described to facilitate closure and repair of soft tissues in the plastic surgery literature [3,8]. For finger flexor tendon repairs, knotless barbed sutures provide comparable strength to standard knotted sutures [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while avoiding local ischemia, [25][26][27][28][29] the continuous suture using barbed sutures allows a comparable or even tighter wound closure overall 30,31 with seemingly comparable cosmetic results. 32 Several clinical trials have suggested a similar complication rate for wound closure with barbed sutures as that with monofilament suture material, for example, in total knee arthroplasty, 21,33 vesicourethral anastomosis, 34 and gynecologic surgery. 35 It is, however, difficult to compare results for an event with a low pretest probability, such as SSIs.…”
mentioning
confidence: 99%
“…The advantages of using non-absorbable barbed sutures are well known and they are the following: they are safe and reproducible with a short learning curve [15]; assistance is not required to maintain suture tension; the suture does not slip [16]; it shortens the total OT [17] and it seems to have similar 30-day outcomes when compared with traditional suture [18].…”
Section: Discussionmentioning
confidence: 99%